Pengaruh Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Luxcrime yang Dimediasi oleh Kepercayaan: Studi Kasus pada Masyarakat Kabupaten Sergai - Putri Rafwani; Hazmanan Khair (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to determine the influence of product quality and promotion on luxury crime purchasing decisions with trust as a mediating variable. The population of this research is all residents of Sergai Regency who have purchased Luxcrime. The sample for this research was 180 respondents. Data analysis used in this research was carried out using the alternative Partial Least Square (PLS) method. The results of the research show: 1) product quality influences the decision to purchase luxcrime, 2) promotion influences the decision to purchase luxcrime, 3) trust influences the decision to purchase luxcrime, 4) product quality influences consumer confidence in luxcrime, 5) promotion influences consumer confidence in luxcrime , 6) trust mediates the influence of product quality on luxury crime purchasing decisions, 7) trust mediates the influence of promotions on luxury crime purchasing decisions in the Sergai district community